Taurine/chenodeoxycholic acid ratio as a potential serum biomarker for low vitamin B 12 levels in humans - Baghel, Madhu; Shi, Sting L.; Patel, Himani; Velagapudi, Vidya; Ali, Abdullah Mahmood; Yadav, Vijay K. (British journal of nutrition, 2024)
Deficiency of vitamin B 12 (B 12 or cobalamin), an essential water-soluble vitamin, leads to neurological damage, which can be irreversible and anaemia, and is sometimes associated with chronic disorders such as osteoporosis and cardiovascular diseases. Clinical tests to detect B 12 deficiency lack specificity and sensitivity. Delays in detecting B 12 deficiency pose a major threat because the progressive decline in organ functions may go unnoticed until the damage is advanced or irreversible. Here, using targeted unbiased metabolomic profiling in the sera of subjects with low B 12 levels v control individuals, we set out to identify biomarker(s) of B 12 insufficiency. Metabolomic profiling identified seventy-seven metabolites, and partial least squares discriminant analysis and hierarchical clustering analysis showed a differential abundance of taurine, xanthine, hypoxanthine, chenodeoxycholic acid, neopterin and glycocholic acid in subjects with low B 12 levels. Random forest multivariate analysis identified a taurine/chenodeoxycholic acid ratio, with an AUC score of 1, to be the best biomarker to predict low B 12 levels. Mechanistic studies using a mouse model of B 12 deficiency showed that B 12 deficiency reshaped the transcriptomic and metabolomic landscape of the cell, identifying a downregulation of methionine, taurine, urea cycle and nucleotide metabolism and an upregulation of Krebs cycle. Thus, we propose taurine/chenodeoxycholic acid ratio in serum as a potential biomarker of low B 12 levels in humans and elucidate using a mouse model of cellular metabolic pathways regulated by B 12 deficiency.